Analysis of the paleomagnetism and rock magnetism of the Surco Intrusion, Peru: an attempt to obtain a Southern Hemisphere reversal record - Weeks, Robin J. (1990)
Investigation of the Surco pluton, a granodioritic body approximately 12 km in diameter and age 20 Ma, located near Lima, Peru, was initiated in order to obtain a geomagnetic reversal record. More than 300 samples provide a complete section through the intrusion. Preliminary results obtained using conventional paleomagnetic techniques indicate that the western part of the pluton records the ambient field behavior well; a consistent reversed direction is followed by a partial reversed to normal transition as one progresses into the core of the intrusion. Plots of NRM vs. IRM(S) demagnetization indicate a steady decrease in the geomagnetic field intensity prior to the reversal. The intrusion does not appear to have recorded the recovery of the normal intensity after the reversal. The existence of a complete section through the intrusion permitted, in principle, the observation of a symmetrical record of the reversal from each side of the pluton. However, the results from the eastern Surco section present a confusing picture and reveal significant variations in rock magnetic and remanence properties along section. Magnetic properties of mineral separates were studied in an attempt to understand variability in the rock as a paleomagnetic recorder. In general, the feldspars contain an unstable magnetization, while the mafic minerals hold a more stable magentization. In the eastern Surco, there are considerable variations in their magnetic properties.